SPECIFIC CHARACTERISTICS OF THE FORMATION OF YOUTH'S MUSICAL THINKING (Scientific journal of the Fergana State University, 2024)
This article expresses thoughts on the influence of art, in particular music, on the human soul in modern society, especially in the conditions of new Uzbekistan, on the formation of musical thinking of young people, educating them in the spirit of national values, fostering patriotism, national traditions, oriental education and upbringing of a harmonious generation glorifying our national art and culture.